Effects of dezocine with ropivacaine on epidural analgesia during labor: a randomized controlled trial - Su, Bin; Qian, Panlian; Zhang, W. P.; Hou, Yi; Shen, Yiyi (Frontiers in Pharmacology, 2025)
BackgroundAdding μ-opioid receptor agonists to local anesthetics are usually used for labor analgesia, while they are associated with pruritus. Kappa opioid agonists (dezocine) are widely used for pain management. Recently, they have emerged as a novel type of potent antipruritic agents. The purpose of this study was to investigate the effects of dezocine with ropivacaine on epidural analgesia during labor.MethodsA total of 120 parturients were randomly divided into two groups (60 cases each). The group D received 0.1% ropivacaine with dezocine 0.2 mg/mL for epidural analgesia while the control group received 0.1% ropivacaine with sufentanil 0.4 μg/mL for epidural analgesia. The systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were monitored. The onset time and duration of analgesia, pain intensity, Bromage scores, delivery outcome, neonatal Apgar scores, and adverse events of mothers and neonates were recorded. Pain intensity was assessed using visual analogue scale (VAS). Umbilical arterial blood was collected for analysis.ResultsThe incidence of itching was lower in the group D than the control group (0% vs. 10%, P = 0.036). The duration of analgesia was longer in the group D (76.1 ± 9.7 vs. 72.1 ± 10.5 min, P = 0.032), and numbers of boluses were fewer in the group D (median, 2 vs.3, P = 0.018). The onset time of analgesia and VAS values were similar between the two groups (all P > 0.05). There were no significant differences in terms of hypotension, bradycardia, motor block, respiratory depression, fetal acidosis, nausea and vomiting between the two groups.ConclusionThis study indicated that the epidural use of dezocine increased the analgesic effect, prolonged the duration of analgesia and decreased the incidence of itching during labor without increasing adverse events of mothers and neonates.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2000035341.